Egress thresholds and wildfire fatalities - Caitlin R. Fong; Carlo W. Broderick; Max A. Moritz; Benjamin S. Halpern (Proceedings of the National Academy of Sciences, 2026)
Avoiding human fatalities during wildfires is a key public policy objective. Outward road access, or the number of egress routes, is widely assumed to influence wildfire fatalities, yet few studies have quantified if or when this factor becomes critical. To address this gap, we assembled a dataset on community-level wildfire fatality counts and combined it with nationally consistent community egress for the United States, finding that cumulative fatalities are sharply concentrated in communities with very few exits, declining steeply to roughly six nonresidential roads, beyond which additional routes confer minimal further risk reduction. Extending this analysis nationally, we mapped all small communities (<50,000 residents) to identify geographic confluence of limited egress and high wildfire hazard, highlighting regions where road constraints could directly amplify fatalities. Across the United States, 17.7 million people live in communities below this critical egress threshold, including 2.5 million in high wildfire hazard areas. Although most high-risk communities are in the western United States, unexpected hotspots appear in Oklahoma, Florida, and Hawai’i. As wildfire hazard continues to expand with climate change, fuel accumulation, and development in the wildland–urban interface, even more communities may be at risk. Targeted investment in road infrastructure, improved evacuation communication and preparedness, and development of preplanned refuge options together offer complementary and actionable pathways to reduce wildfire fatalities and build nationwide resilience.